2010
DOI: 10.1510/icvts.2009.224279
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonectomy for lung cancer over the age of 75 years: is it worthwhile?☆

Abstract: The objective of the study was to evaluate the outcome in elderly patients (>75 years) submitted to pneumonectomy for lung cancer. Records of 40 elderly patients, who underwent pneumonectomy at our Institution from 1990 to 2008, were retrospectively reviewed. This group was compared with 289 younger patients submitted to pneumonectomy in the same period. In the older group median age was 77 years (range 75-84 years), 16 were right-side procedures. In the younger group median age was 62 years (range 24-74 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 14 publications
3
10
0
1
Order By: Relevance
“…This is mainly related to the prolonged life expectancy in the whole population, as well as the possibility of earlier and more appropriate diagnostics and technological development of modern medicine. Patients over the age of 75 years already constitute a significant proportion of the lung cancer population, reaching approximately 30–50% [ 2 , 6 ]. Although surgical treatment of elderly patients poses a significant challenge for thoracic surgeons, as it is associated with a higher risk of postoperative morbidity and mortality compared to younger patients, it is still the best choice for the treatment of lung cancer in elderly patients [ 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly related to the prolonged life expectancy in the whole population, as well as the possibility of earlier and more appropriate diagnostics and technological development of modern medicine. Patients over the age of 75 years already constitute a significant proportion of the lung cancer population, reaching approximately 30–50% [ 2 , 6 ]. Although surgical treatment of elderly patients poses a significant challenge for thoracic surgeons, as it is associated with a higher risk of postoperative morbidity and mortality compared to younger patients, it is still the best choice for the treatment of lung cancer in elderly patients [ 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radical pulmonary resections in that age group of patients are associated with both a higher rate of serious and life-threatening early postoperative complications as well as an uncertain long-term postoperative outcome. In numerous reports, it is emphasised that age alone is not a contraindication for surgical treatment of elderly patients; careful selection of those patients as well as an interdisciplinary assessment prior to surgery should be performed [2 5 ]. Patients over 75 years of age, who, in addition, often have already exceeded the average life expectancy, in the Polish population on average 77.4 years, are the subject of discussion concerning the most appropriate choice of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…reported that right side PN was strongly related to perioperative and six month mortality. Zuin et al . reported that PN appeared to be justified even in patients older than 75 years, because short and long‐term outcomes could be acceptable and comparable with those of younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Banganand et al 16 and Rodriquez et al 17 reported that right side PN was strongly related to perioperative and six month mortality. Zuin et al 18 reported that PN appeared to be justified even in patients older than 75 years, because short and long-term outcomes could be acceptable and comparable with those of younger patients. However, a right side procedure was related to a high mortality rate (P < 0.01), therefore, there were few right side PNs in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Esta tendencia a operar a pacientes ancianos se fundamenta en el axioma de que la decisión de una resección pulmonar con intenciones curativas no debe basarse únicamente en la edad cronológica de pacientes. Existen publicaciones de cirugías de resección en pacientes octogenarios, seleccionados adecuadamente en base a pruebas funcionales y con comorbilidades razonables, que concluyen que la morbimortalidad es similar a la de los pacientes más jóvenes[336][337][338][339] . Además es importante recordar que la resección completa del tumor, cuando es posible, ofrece mejores resultados (independientemente de la edad del paciente) en comparación a la radioterapia o quimioterapia en términos de supervivencia340 .El IMC promedio de la muestra fue de 25,6, la diferencia entre hombres y mujeres no fue significativa, se encontró que el 58% de pacientes tenían sobrepeso y obesidad, aunque tan solo el 13% de pacientes presentaron un IMC mayor de 30 y no se tiene constancia de pacientes operados con obesidad mórbida.…”
unclassified